2011
DOI: 10.1111/j.1755-5949.2011.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Anxiety

Abstract: SUMMARYThis review aims to examine the volume and quality of the evidence base which supports the use of acupuncture in the treatment of anxiety disorders. A literature review was conducted using Pubmed, Google scholar, AMED, BMJ, Embase, Psychinfo, Cochrane library, Ingenta connect, and Cinahl databases. Keywords were "anxiety," "anxious," "panic," "stress," "phobia," and "acupuncture" limited to year 2000 onwards and English language where available. The quality of research examining the use of acupuncture i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 40 publications
3
43
0
1
Order By: Relevance
“…The results in the present study are in line with previous reports indicating that acupuncture can reduce symptoms of anxiety [42] and depression [22,23,25] and improve HRQoL [28,30,31] in other conditions than PCOS. The effect of acupuncture was more pronounced on anxiety symptoms and there was a clear tendency of decrease within the acupuncture group immediately after the treatment period but it did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…The results in the present study are in line with previous reports indicating that acupuncture can reduce symptoms of anxiety [42] and depression [22,23,25] and improve HRQoL [28,30,31] in other conditions than PCOS. The effect of acupuncture was more pronounced on anxiety symptoms and there was a clear tendency of decrease within the acupuncture group immediately after the treatment period but it did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…The other involves the use of auricular acupuncture, based most often either on National Acupuncture Detoxification Association (NADA) protocol or the Nogier style (i.e., Shen Men, Tranquilizer, and Master Cerebral Point). 9 In one study, using both body points and auriculotherapy were found to be equally effective in alleviating preoperative anxiety. 15 All of the above methodstreating the Liver, Heart, and Mind-are commonly combined in the treatment of anxiety in clinical practice.…”
Section: Tcm Treatment Of Anxietymentioning
confidence: 98%
“…8 Beta-blockers are also used to treat anxiety, especially social phobia, but also have weight gain and sexual dysfunction as potential side effects. 9 Acupuncture has been shown to be promising in treating anxiety and anxiety disorders in several clinical studies, 10 and has been shown to be as effective as cognitive behavioral therapy in the treatment of PTSD. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown acupuncture may be a viable alternative to drugs treatments for anxiety and depression. [12,13] …”
Section: Anxiety and Depressionmentioning
confidence: 99%